2018
DOI: 10.1074/jbc.ra118.003049
|View full text |Cite
|
Sign up to set email alerts
|

Proliferating cell nuclear antigen interacts with the CRL4 ubiquitin ligase subunit CDT2 in DNA synthesis–induced degradation of CDT1

Abstract: Edited by Xiao-Fan Wang During DNA replication or repair, the DNA polymerase cofactor, proliferating cell nuclear antigen (PCNA), homotrimerizes and encircles the replicating DNA, thereby acting as a DNA clamp that promotes DNA polymerase processivity. The formation of the PCNA trimer is also essential for targeting the replication-licensing protein, chromatin-licensing, and DNA replication factor 1 (CDT1), for ubiquitin-dependent proteolysis to prevent chromosomal DNA re-replication. CDT1 uses its PCNA-intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Once this bistable switch is engaged, the persistent activity of CRL4 Cdt2 at aRCs during S phase generates hysteresis through the persistent degradation of p21, preventing it from interfering with DNA replication and insulating S phase progression from the influence of DNA damage . In addition to p21, it is likely that other cell cycle regulators that are degraded by CRL4 Cdt2 (e.g., Cdt1 ) should also exhibit hysteresis at the G1/S transition.…”
Section: Integration Of the Rb‐e2f Switch With Other Bistable Switchesmentioning
confidence: 99%
“…Once this bistable switch is engaged, the persistent activity of CRL4 Cdt2 at aRCs during S phase generates hysteresis through the persistent degradation of p21, preventing it from interfering with DNA replication and insulating S phase progression from the influence of DNA damage . In addition to p21, it is likely that other cell cycle regulators that are degraded by CRL4 Cdt2 (e.g., Cdt1 ) should also exhibit hysteresis at the G1/S transition.…”
Section: Integration Of the Rb‐e2f Switch With Other Bistable Switchesmentioning
confidence: 99%
“…CRL4 DDB2 mediated degradation of DDB2 and p21 is PCNA-dependent, and PIP box contributes to the interaction between DDB2 and PCNA [ 41 ]. In addition, CDT2 is also a PIP box containing protein, and can directly bind to PCNA through the PIP box [ 6 , 42 ]. Our previous work showed that PIP box in CDT2 is essential for CDT1 degradation [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, CDT2 is also a PIP box containing protein, and can directly bind to PCNA through the PIP box [ 6 , 42 ]. Our previous work showed that PIP box in CDT2 is essential for CDT1 degradation [ 42 ]. We supposed that the ubiquitination-mediated degradation of CDT2 by CRL4 DDB2 ligase is in a PCNA-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, CDT2 is also a PIP box containing protein, and can directly bind to PCNA through the PIP box [6,43]. Our previous work showed that PIP box in CDT2 is essential for CDT1 degradation [43]. We supposed that the ubiquitination-mediated degradation of CDT2 by CRL4 DDB2 ligase is in a PCNA-dependent manner.…”
Section: Ddb2 Interacts With Cdt2 and Mediates Its Ubiquitinationmentioning
confidence: 94%
“…The ubiquitination-mediated degradation of CDT2 by CRL4 DDB2 is independent of PCNA CRL4 DDB2 mediated degradation of DDB2 and p21 is PCNA-dependent, and PIP box contributes to the interaction between DDB2 and PCNA [42]. In addition, CDT2 is also a PIP box containing protein, and can directly bind to PCNA through the PIP box [6,43]. Our previous work showed that PIP box in CDT2 is essential for CDT1 degradation [43].…”
Section: Ddb2 Interacts With Cdt2 and Mediates Its Ubiquitinationmentioning
confidence: 97%